Adipocytokines and Insulin Resistance: The possible role of lipocalin-2, retinol binding protein-4, and adiponectin - Esteve, Eduardo; Ricart, Wifredo; Fernández-Real, José Manuel (Diabetes care, 2009)
Conversely, LCN2 has recently been claimed to display anti-inflammatory effects, so that increased LCN2 levels in obesity and insulin resistance may constitute a protective mechanism against inflammation (10). [...] LCN2 upregulated peroxisome proliferatoractivated receptor (PPAR)-Î³ and its target genes, adiponectin, leptin, fatty acid synthase, and lipoprotein lipase in adipocytes.